ANALYSIS OF COMMUNITY CASH WAQF INTENTION TO SUPPORT SUSTAINABLE DEVELOPMENT GOALS (SDGs): THEORY PLANNED BEHAVIOUR APPROACH - Alif Khuwarazmi Maulana Julendra; Silvi Sri Mulyani; Arfi Mulyasa Insani (Airlangga International Journal of Islamic Economics and Finance, 2021)
The SDGs outline 17 goals that are part of the sustainable development agenda. One of the efforts that can be made to alleviate poverty around the world is by utilizing "endowment funds". In Indonesia, financing innovation to alleviate poverty can be done through cash waqf. However, the facts on the ground show that the huge potential for cash waqf cannot be optimally absorbed. Therefore, this study aims to explore and test empirically the extent to which the Indonesian people intend to optimize the potential of cash waqf in an effort to support financing and achieve the goal of poverty alleviation in Indonesia. This is done by identifying the factors that influence the intention of the Indonesian people to distribute cash waqf and correlating this with the influence of public knowledge about waqf, especially the cash waqf itself. The method used in this study is a quantitative method by collecting primary data from as many as 316 Muslim respondents throughout Indonesia. The questionnaire used is the adoption of Theory Planned Behavior (TPB) with the addition of several variables that affect intention. This approach is used to determine the community's intention to distribute cash waqf. The results of the study indicate the consideration of Indonesian Muslim knowledge in the influence of the intention to do cash waqf, and the results show that there is no significant influence between attitudes (attitudes towards) and people's intention to donate money.